THE ROLE OF MOVEMENT AND PHYSICAL ACTIVITIES IN EARLY ENGLISH EDUCATION (Лучшие интеллектуальные исследования, 2025)
ANNOTATION   This topic investigates the pedagogical value of integrating movement and physical activities into early English language education. Grounded in theories of embodied cognition and multisensory learning, it examines how kinesthetic activities can enhance linguistic development in young learners. Research highlights that physical movement supports cognitive functions such as memory, attention, and language retention (Ratey, 2008; Diamond, 2015). Methods like Total Physical Response (Asher, 1977) exemplify the efficacy of combining language input with motor activity, demonstrating improved vocabulary acquisition and sentence comprehension in early learners.Furthermore, movement-based learning strategies promote active engagement, reduce anxiety, and create a more inclusive classroom for kinesthetic and neurodiverse learners (Tomlinson, 2014). Activities such as action songs, storytelling with gestures, dramatization, and educational games foster both verbal and non-verbal communication skills. These strategies are also linked to enhanced social interaction, emotional development, and cooperative learning (Piaget, 1962; Vygotsky, 1978), which are crucial in the early stages of language acquisition.This approach aligns with the holistic model of early childhood education, suggesting that cognitive, physical, social, and emotional development are interconnected. Thus, the integration of movement into English language teaching not only improves linguistic outcomes but also supports overall child development.